Challenges facing educational support and enrichment initiatives: The need for guidelines and clarity - Maddock, L.; Maroun, W. (South African Journal of Higher Education, 2021)
The purpose of this article was to consider the need for guidelines and consistent criteria for support and enrichment of students facing the transition from secondary school to tertiary education, and some of the challenges involved. The article’s narrow context is language and accounting; the wider context is challenges faced by most students and educators in the above key phases. Through a brief review of initiatives at two prominent universities in South Africa and an analysis of 17 interviews with teachers, tutors and lecturers working with adolescents, the researchers have sought to identify several existing challenges. Data collected indicate that most stakeholders acknowledge the importance of support / enrichment. Many, though, are unsure of how to achieve the desired outcomes of programmes. This conflict seems to lie in a lack of focused guidelines. There seems to be a need for consistency: this will strengthen initiatives as the successes and failures of educators and policy makers will help to form a framework for work in the immediate future.